2022
DOI: 10.1111/jch.14532
|View full text |Cite
|
Sign up to set email alerts
|

Isolated nocturnal hypertension in relation to host and environmental factors and clock genes

Abstract: Isolated nocturnal hypertension (INH) is a special type of out-of-office hypertension. Its determinants and pathophysiology remain unclear. In a nested case-control study, we intend to investigate the host, environmental, and genetic factors in relation to INH. Among 2030 outpatients screened from December 2008 till June 2015, 128 patients with INH were identified, and then 128 normotensives were matched according to sex and age. INH was an elevated nocturnal blood pressure (BP ≥120/70 mmHg) in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The determinants of nocturnal hypertension include genetic factors, environmental factors, sleep, salt, medical diseases (sleep apnea, diabetes, chronic kidney disease, etc), and antihypertensive medication (Figure 1). Huang JF and associates found that higher nighttime heart rate, shorter sleep duration, and higher humidity were all determinants of isolated nocturnal hypertension, but they found no association with genetic factors 5 . Higher nighttime heart rate and increased heart rate variability are known to be associated with sleep apnea and heart failure.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…The determinants of nocturnal hypertension include genetic factors, environmental factors, sleep, salt, medical diseases (sleep apnea, diabetes, chronic kidney disease, etc), and antihypertensive medication (Figure 1). Huang JF and associates found that higher nighttime heart rate, shorter sleep duration, and higher humidity were all determinants of isolated nocturnal hypertension, but they found no association with genetic factors 5 . Higher nighttime heart rate and increased heart rate variability are known to be associated with sleep apnea and heart failure.…”
Section: Figurementioning
confidence: 99%
“… 3 , 4 In this issue, Huang JF and associates extensively investigate the association between isolated nocturnal hypertension and determinates such as clock genes, environmental factors, and patient characteristic. 5 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Given that ABPM is expensive and not quite accessible [ 15 , 16 , 17 ], it is crucial to establish that both INH and MNH are frequently sufficient for attempting to detect them, and it is also very important to determine characteristics of these conditions that would make performing an ABPM worth it. Moreover, INH and MNH have been studied primarily in Asian populations [ 11 , 18 ]. Data on other populations are scarcer.…”
Section: Introductionmentioning
confidence: 99%